Fenomenologia – wprowadzenie w lekturę tekstu Edmunda Husserla „Phänomenologie (Der Encyclopaedia Britannica Artikel)” - Bekrycht, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The article presents in the synthetic way the major assumptions of phenomenology as the philosophical movement. The author has delineated two tasks. Firstly, introduction to the major issues of phenomenology and underlining important origins of phenomenology, i.e. Edmund Husserl’s work – Logical Investigations. Secondly, introduction to the reading of an important text (unpublished in Polish by now) that describes the basic foundations of this phenomenological movement, which have been developed by its creator.